Central nervous system complications in adult cystinosis patients. Issue 2 (18th September 2019) - Servais, Aude; Saitovitch, Ana; Hummel, Aurélie; Boisgontier, Jennifer; Scemla, Anne; Sberro‐Soussan, Rebecca; Snanoudj, Renaud; Lemaitre, Hervé; Legendre, Christophe; Pontoizeau, Clément; Antignac, Corinne; Anglicheau, Dany; et al.
Abstract: Little is known about the long‐term progression of adult nephropathic cystinosis patients. Our objective was to study central nervous system complications in cystinosis patients in the era of early cysteamine treatment, using advanced neuroimaging techniques. Neurological examination and multimodal brain 3 Tesla MRI were performed in 21 adult cystinosis patients, including 18 infantile cystinosis patients, 20 controls matched for age and renal function, and 12 healthy controls. Differences in gray matter volume and rest cerebral blood flow (CBF) using arterial spin labeling sequence were investigated using whole‐brain voxel‐based approach. Median age was 33.8 years (18.7‐65.8). Seven patients (38.9%) presented with at least one central nervous system clinical abnormality: two (11.1%) with seizures, three (16.7%) with memory defects, five (27.8%) with cognitive defect, and one (5.5%) with stroke‐like episode. These patients had a worse compliance to treatment (compliance score 2 vs 1, P = .03) and received a lower median cysteamine dose (0.9 g/day vs 2.1 g/day, P = .02). Among patients with infantile cystinosis, 13 (72.2%) showed cortical atrophy, which was absent in controls, but it was not correlated with symptoms. Cystinosis patients showed a significant gray matter decrease in the middle frontal gyrus compared with healthy controls and a significant negative correlation between the cystine blood level and rest CBF was observed in the right superior frontal gyrus, a region associated with executive function. Compliance to cysteamine treatment is a major concern in these adult patients and could have an impact on the development of neurological and cognitive complications.